Design of Geographic Information System Based on Android for Culinary Tourism in Pedan District, Indonesia - Ekowati, Maria Atik Sunarti; Widianto, Widianto (International Journal of Global Operations Research, 2021)
Pedan City is a sub-district city located in the Klaten Regency area and has always been a culinary tourism object for tourists or residents in the Pedan area and its surroundings. The main problem that arises is when there are more and more culinary attractions in the city of Pedan sub-district, but there is less detailed information about these culinary attractions. The main objevtive of this work is to provide location information tourism in the Pedan area easily and simply because it can be operated anywhere the user is using an android-based mobile device. The method used in this research is the Waterfall method. The results of the study are expected to increase culinary tourism in the city of Klaten district, especially Pedan sub-district, as well as interest for tourists or residents in the city of Pedan sub-district to be interested in visiting culinary tourism objects in the Pedan city area